PENINGGALAN KOLONIAL DI KABUPATEN TELUK BINTUNI - Mene, Bau (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
Colonial relics found in Teluk Bintuni Regency is the oil tank, warehouse logistics, housing, oil wells, oil pump, housing, health department officials, teacher housing, cottages, housing authorities, airports, harbors and swimming pool. From the results of research conducted showed that the remnants of colonial buildings built by the Dutch government is to support the smooth operation of petroleum exploration in Teluk Bintuni Regency. Exploration conducted in Kampung Mogoi and Wasian. Petroleum exploration undertaken by the company NNGPM, which is a joint of some famous international companies owned by the Netherlands and the United States.